importance at Oko-Oba abbatoir,Lagos state (2010)
Meat inspection in abbatoirs plays a fundamental role in identifying zoonotic diseases in animals slaughtered for human consumption. This study was carried out to review the current status of tuberculosis annd other diseases of public health importance in slaughtered cattle at Oko-Oba abbatoir,Lagos state over a period of four years (2004-2007). A total of 1, 154. 757 cattle were slaughtered from which 22, 073 (1.91%) HAD PATHOLOGICAL LESIONS: with 4, 734 (0.41%) and 17, 339 (1.50%) being due to tuberculosis and other diseases of public health importance respectively. The overall infection rate varied significantly with seasons of the year (p< 0.05, xsquare=25.76). similarly, the 1.50% for the non-tuberculosis diseases comprising fascioliasis (0.67%), myiasis(0.42%), dermatophilosis (0.30%) and cysticercosis (0.11%) differs significantly from the 0.41% recorded for tuberculosis (p<0.05). therefore showing more losses attributed to these other diseases. Our findings show that approximately two out of every 100 cattle slaughtered at this abbatoir pose potential health risks to the consumers in the state. Hence, the government and other stakeholders in the livestock industry need to join efforts at controlling and possibly eradicating these diseases fron the cattle population.